2013
DOI: 10.1177/0363546513484127
|View full text |Cite
|
Sign up to set email alerts
|

Bone–Patellar Tendon–Bone Autograft Versus Allograft in Outcomes of Anterior Cruciate Ligament Reconstruction

Abstract: Patients undergoing ACL reconstruction with BPTB autografts demonstrate lower rates of graft rupture, lower levels of knee laxity, and improved single-legged hop test results and are more generally satisfied postoperatively compared with patients undergoing reconstruction with allograft BPTB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(192 citation statements)
references
References 114 publications
4
181
2
5
Order By: Relevance
“…Allograft ACL reconstruction outcome reports have used hamstring 15,33,34 and BPTB allografts without reporting the type of processing used, 12,35 looked at all types of allografts, 7,25 or lumped all allografts together and failed to report the type of allograft used. [36][37][38] It cannot be assumed that all allografts are equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…Allograft ACL reconstruction outcome reports have used hamstring 15,33,34 and BPTB allografts without reporting the type of processing used, 12,35 looked at all types of allografts, 7,25 or lumped all allografts together and failed to report the type of allograft used. [36][37][38] It cannot be assumed that all allografts are equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…However, two meta-analyses comparing the two main graft types (BPTB vs. ST) have demonstrated that a SSD superior to 3 mm was less frequent in BTPB compared to ST grafts [95,96]. Regarding the use of allografts, some authors reported similar outcomes compared to autografts [97,98], while others suggested that they may be inferior [99]. As for the double-bundle HS autograft technique, there are indications suggesting that it may be superior in terms of sagittal and rotational laxity [100][101][102].…”
Section: Knee Laxity After Anterior Cruciate Ligament Reconstructionmentioning
confidence: 99%
“…knee pain after BPTB harvest [9,24], higher failure rates and poorer clinical outcome scores associated with hamstring tendon grafts that are less than 8 mm in diameter [8,19,20,26], and with the use of allografts [5,17,22].…”
mentioning
confidence: 99%